2013
DOI: 10.2478/aoas-2013-0057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Supplementation with Herbal Extracts on Broiler Chicken Welfare / Wpływ Dodatku Do Wody Ekstraktów Ziołowych Na Dobrostan Kurcząt Brojlerów

Abstract: This study investigated the effect of adding extracts from selected herbs to water on alleviation of broiler stress associated with intensive production, and thus on improvement of welfare. In experimental groups (II, III and IV), alcoholic extracts from chamomile inflorescence (Matricaria chamomilla L.), lemon balm (Melissa officinalis L.) or from St John’s wort (Hypericum perforatum L.), respectively, were added to water drinkers (2 ml ∙ l-1 water) from 21 to 35 days of rearing for 5 h/day. Throughout the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The addition of agrimony extract to poultry nutrition can protect fatty acids in meat against oxidation. It is possible to provide the extract through a water source with high efficiency [71]. A significantly higher increase in MDA concentration was observed in the meat of the experimental group due to a higher amount of PUFA in those muscles.…”
Section: Discussionmentioning
confidence: 95%
“…The addition of agrimony extract to poultry nutrition can protect fatty acids in meat against oxidation. It is possible to provide the extract through a water source with high efficiency [71]. A significantly higher increase in MDA concentration was observed in the meat of the experimental group due to a higher amount of PUFA in those muscles.…”
Section: Discussionmentioning
confidence: 95%
“…A way of enhancing the efficacy of plant extracts may be the water supplementation, which ensures uniform mixing into water, uniform intake by birds and to avoid wastage [10]. Skomorucha and Sosnówka-czajka [11] also reported that the response of broilers to the water supplementation with certain herbs was positive in terms of growth performance, physiological response to stress and welfare. Therefore, this study was conducted to meet consumer preference for safe, hygienic, less prone to oxidative processes and antibiotic-free poultry meat.…”
Section: Introductionmentioning
confidence: 99%
“…Rabbits were given BD + 0.5 ml g/kg. Compared to the other groups, chamomile oil consumed the most feed during the entire duration (Skomorucha and Sosnówka-Czajka, 2013). Likewise, Simonová et al (2007) discovered that chamomile oil is a viable substitute for stopping and managing bacterial and parasite illnesses and enhancing rabbits' overall health.…”
Section: Growth Performancementioning
confidence: 99%